Evaluation Analysis and Key Index System Construction of Urban Public Management Service Quality Based on Grey Judgment Method. (27th September 2022) - Chen, Zimeng
Abstract : The development of today's society has entered an era dominated by technology and efficiency, leading enterprises and governments to overemphasize the role of efficiency in the process of rapid development, while ignoring the fundamental goal of social development. The degree of urbanization has increased significantly, but the problems existing in the city are becoming more and more serious, especially the neglect of public services, which has caused great dissatisfaction. This paper firstly compares and synthesizes the performance of several methods to obtain that the grey judgment method is more suitable for this paper; that is, the grey judgment method is used to analyze the evaluation of urban public management service quality and to construct the key index system. The two-level indicators are all in line with the standard after screening the indicators by the method; the first-level indicators have the largest weight in the assess of the quality of urban common management services, and equipment management is considered to be the most important, followed by cultural construction, emergency management, greening management, and sanitation management; among the secondary indicators, the public health portfolio has the largest weight value, with a combined weight of 0.0989, followed by timely maintenance, quality of green vegetation, accident treatment, water and sewage treatment, natural disaster treatment, maintenance quality, garbage disposal, daily maintenance, the quality of cultural facilities, the daily maintenance of greening, and the quality of cultural activities; experts scored the indicators to get the highest score for equipment management, with a score of 0.7799, followed by emergency management, sanitation management, greening management, and cultural construction. By examining the quality of urban public services, it can more respond to the needs of national for public serving, and it can more effectively facilitate the future growth of the town and improve the overall level of community services.